Examining the influence of leverage, liquidity, and corporate social responsibility on the financial performance of Nifty pharma companies - Javed, Sumbul; Husain, Firoz; Uddin, Moin (Edelweiss Applied Science and Technology, 2025)
The idea of CSR has sparked much discussion across several domains of corporate finance, particularly regarding its potential to enhance a company's financial performance. The main objective of this research is to illustrate the impact of leverage, liquidity, and CSR on the financial performance of Nifty Pharma companies over the ten years from 2014 to 2023. The research employed panel fixed effects regression analysis to examine the effects of CSR, leverage, and liquidity on key financial metrics, Return on Assets (ROA) and Return on Equity (ROE), while controlling for firm size and sales growth. The findings indicate a statistically significant negative impact of CSR on ROE, implying that CSR initiatives may not immediately improve shareholder profits in the short term within the pharmaceutical industry. Conversely, financial leverage and liquidity have consistent and statistically significant impacts on financial performance. The results highlight that proficient management of leverage and liquidity is essential for maintaining financial stability. Although CSR may provide long-term advantages, it sometimes lacks quick financial returns, particularly in emerging nations like India. Policymakers need to implement CSR incentives and regulatory frameworks. Companies must intentionally incorporate CSR while managing liquidity and leverage to improve sustainability and attract socially responsible investors.